A Comparative Study of Cymbopogon citratus Volatile Oil by Conventional Method Versus Enzyme Pre-Treatment. Issue 3 (4th May 2017) - Rashmi,; Bhardwaj, Sapna; Gupta, P.K.
Abstract: The objective of the study is to evaluate the impact of enzymatic pre-treatment on chemical composition of Cymbopogon citratus leaves volatile oil. Enzymatic pre-treatment has been considered as a novel and an effective way to release bounded compounds and increase overall yield. Lemongrass leaves with enzymatic pre-treatment with enzymes viz . β-galactosidase and cellulase yielded 0.82 % and 0.91 % volatile oil respectively. While, with mixture of enzymes (β-glactosidase and cellulase), the yield of volatile oil was 0.97 %. GC-MS analysis of enzymatic per-treated oil showed thirty three chemical constituents (99.5 %) with significant variation in area percentage of major constituents. However, in conventional hydro-distillation method, twenty two chemical constituents (72.4 %) were present. On comparison of enzyme aided extraction using mixture of enzymes showed the presence of some new chemical constituent's viz .1R α-pinene (0.43 %), α-phellendren (0.46 %), D-limonene (0.53 %), and citronellol (0.64 %) and a very significant increase in percentage of major components like α-citral, β-citral, geraniol, and β-Linalool.